NutriCancer: A French observational multicentre cross-sectional study of malnutrition in elderly patients with cancer. Issue 1 (January 2018) - Lacau St Guily, Jean; Bouvard, Éric; Raynard, Bruno; Goldwasser, François; Maget, Brigitte; Prevost, Alain; Seguy, David; Romano, Olivier; Narciso, Bérengère; Couet, Charles; Balon, Jean-Michel; Vansteene, Damien; et al.
Abstract: Objectives: To compare the prevalence of malnutrition and nutritional management between elderly (≥ 70 years old) and younger patients (< 70 years) with cancer. Patients and Methods: This is a post-hoc analysis of NutriCancer 2012 study; a one-day cross-sectional nationwide survey conducted to assess malnutrition in adult patients with cancer in France. Patients diagnosed with cancer at the study date in both inpatient and outpatient settings were included. Data collection was performed by means of questionnaires completed by the physician, the patient and the caregiver. Results: This post-hoc analysis compared 578 elderly patients (27.6%) vs . 1517 younger patients (72.4%). There were significant differences in cancer localization between the groups particularly in gastrointestinal cancer (27% in younger patients vs. 42% in elderly), breast cancer (17% vs 8% in elderly) and oropharyngeal (15% vs. 9% in elderly). Weight loss was significantly more reported in the elderly than in younger patients (73.6% vs. 67.6%, p = 0.009). Elderly patients were more frequently malnourished than younger patients (44.9% vs. 36.7%, p = 0.0006). Food intake was comparable between the groups; however, physicians overestimated the food intake, particularly in the elderly. The malnutrition management was more frequently proposed in elderly, as dietary advice and oral nutritional supplements, than in younger patients; however, enteral nutrition was significantly less undertaken in the elderly. Conclusion: Malnutrition is prevalent in elderly patients with cancer, and more frequent than in younger patients. There is a need for an early integration of the nutritional counselling in patients with cancer, and particularly in the elderly.